Analysis of students' legal awareness for bullying prevention in Surakarta schools - Rejekiningsih, Triana; Taher, Maram (Universitas Negeri Yogyakarta, 2025)
This study investigates the legal awareness of students in Surakarta junior high schools concerning preventing bullying, intending to promote quality education in alignment with Sustainable Development Goals (SDGs). The research explores students' understanding, potential, and awareness of bullying prevention using qualitative and descriptive methods. Bullying encompasses various forms of violence, including physical, verbal, social, and cyber forms, often characterised by intimidation. The findings revealed that 90.99% of students reported experiencing bullying, predominantly verbal, with 53.25% subjected to discriminatory behaviour. Although 70% acknowledged the occurrence of physical and verbal violence, there was a noted deficiency in effective preventive measures, indicating a low level of awareness regarding bullying prevention. The study highlights the urgent need for improved awareness and preventive measures, making the audience feel the urgency and importance of the issue. It also underscores the vital role of schools and communities in enhancing legal awareness among students.